Synthesis of Aryl Iodides from Arylhydrazines and Iodine - Dong, Chun-ping (ACS Omega, 2018)
[Image: see text] A metal- and base-free method is developed for the synthesis of aryl iodides from arylhydrazine hydrochlorides and iodine. A wide variety of aryl iodides can be conveniently synthesized by an equimolar reaction of arylhydrazine hydrochlorides and I(2) in dimethyl sulfoxide at 60 °C for 6 h. In the iodination step, arylhydrazines are oxidized by iodine to form arenediazonium salts, which undergo single-electron transfer from iodide anion to give aryl and iodine radicals; subsequent combination of them affords the corresponding aryl iodides.